2018
DOI: 10.1177/0040517518773370
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the bee-repellent properties of cotton fabrics treated with microencapsulated essential oils

Abstract: In this study, to produce single-use bee-repellent fabrics, a variety of essential oils were encapsulated with gum arabic wall material at a 1:5 ratio of wall to the core substance. The following core substances were used: lavender oil, laurel oil, fennel oil, N, N-diethyl-3-methylbenzamide (DEET), lavender + laurel oil, lavender + fennel oil, laurel + fennel oil, lavender + fennel + laurel oil, lavender oil + DEET, fennel oil + DEET and laurel oil + DEET. Lavender, fennel and laurel oils were analyzed by high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
5
1
Order By: Relevance
“…In contrast, DEET has a higher hydrophobicity, less ionic interaction force with polymeric walls resulting in the relatively smaller size of microcapsules. DEET-MCs and Picaridin-MCs synthesized by complex coacervation in the present work are smaller to those found with MCs loaded with DEET prepared from simple coacervation of solely gum Arabic, which resulted in a wide variety of microcapsule sizes observed (ranging from 1-68 µm) 19 .…”
Section: Characterization Of the Microcapsulescontrasting
confidence: 81%
See 1 more Smart Citation
“…In contrast, DEET has a higher hydrophobicity, less ionic interaction force with polymeric walls resulting in the relatively smaller size of microcapsules. DEET-MCs and Picaridin-MCs synthesized by complex coacervation in the present work are smaller to those found with MCs loaded with DEET prepared from simple coacervation of solely gum Arabic, which resulted in a wide variety of microcapsule sizes observed (ranging from 1-68 µm) 19 .…”
Section: Characterization Of the Microcapsulescontrasting
confidence: 81%
“…The ME formulation of DEET showed repellent activity against Culex quinquefasciatus under laboratory conditions 18 . Eyupoglu et al 19 reported the microencapsulation of DEET via a simple coacervation method. DEET was encapsulated with gum Arabic wall material at a 1:5 ratio of wall to the core substance.…”
Section: Introductionmentioning
confidence: 99%
“…Microencapsulated insecticides [57], acaricides [58], insect repellents [59,60] and combined bioinsecticide-insect repellent compounds [61,62] have been used in textiles to reduce volatility, prolong release and decrease washfastness of active compounds from textile substrates.…”
Section: Microcapsules In Functional Textile Productsmentioning
confidence: 99%
“…On the other side, the encapsulation of fragrances and aromas was pursued recently for the fabrication of “smart textiles” with additional functional properties [ 115 ], such as antibacterial, UV protection, moisturising and skin treatments, body temperature regulation and insect repellence, depending on the action of the encapsulated fragrances, aromas or EOs [ 116 , 117 , 118 , 119 ]. An example of encapsulation for UV protection in textiles is from the work of Chen et al, in which the one-step fabrication of cellulose/silica hybrid microcapsules via an emulsion solvent diffusion method was reported [ 120 ].…”
Section: Applications Of Micro-/nanoencapsulated Fragrances and Flmentioning
confidence: 99%